2017
DOI: 10.1073/pnas.1700655114
|View full text |Cite
|
Sign up to set email alerts
|

Combined epigenetic and differentiation-based treatment inhibits neuroblastoma tumor growth and links HIF2α to tumor suppression

Abstract: Neuroblastoma is a pediatric cancer characterized by variable outcomes ranging from spontaneous regression to life-threatening progression. High-risk neuroblastoma patients receive myeloablative chemotherapy with hematopoietic stem-cell transplant followed by adjuvant retinoid differentiation treatment. However, the overall survival remains low; hence, there is an urgent need for alternative therapeutic approaches. One feature of high-risk neuroblastoma is the high level of DNA methylation of putative tumor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 66 publications
(68 reference statements)
3
69
0
Order By: Relevance
“…Our analysis of another MES line, GI-MEN, did not however support the notion that induction of proliferation by Wnt is solely attributable to a MES identity. We have previously shown that SK-N-AS cells are also quite different from SK-N-BE(2)-C and SH-SY5Y cells in terms of their genomewide DNA methylation pattern [69], and the epigenetic identity of SK-N-AS has been shown to influence their differentiation response [28,70]. Thus further analysis at the epigenetic and proteomic level with a broad range of neuroblastoma cell lines will be 2 1 necessary to precisely identify the determinants of the phenotypic responses to Wnt signalling by neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis of another MES line, GI-MEN, did not however support the notion that induction of proliferation by Wnt is solely attributable to a MES identity. We have previously shown that SK-N-AS cells are also quite different from SK-N-BE(2)-C and SH-SY5Y cells in terms of their genomewide DNA methylation pattern [69], and the epigenetic identity of SK-N-AS has been shown to influence their differentiation response [28,70]. Thus further analysis at the epigenetic and proteomic level with a broad range of neuroblastoma cell lines will be 2 1 necessary to precisely identify the determinants of the phenotypic responses to Wnt signalling by neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found genes encoding neuronal proteins were induced by Wnt3a/Rspo2, including several neurotransmitter receptors (HTR1E, HTR2B, NPY2R, ADRA2A and OPRM1), neurofilament protein M (NEFM), and transcription factors involved in differentiation of the neural crest, including MSX1 and MSX2 [41]. EPAS1/HIF-2α, which was very recently associated with differentiation of neuroblastoma [28] was 1 1 also upregulated after treatment. ASCL1, which is one of the few down-regulated genes amongst the DEGs, is also involved in neuronal differentiation [42], with mRNA downregulation also observed with retinoic acid induced differentiation of neuroblastoma cells [43].…”
Section: Immunoblotting and Immunohistochemistrymentioning
confidence: 96%
See 1 more Smart Citation
“…FusionCatcher (18) was applied to detect the fusion transcripts in paired-end RNA-seq data. Reads were mapped to hg19 and differential expression analysis was performed as described in (42). For enrichment analysis in Figure 1C, only fusions occurring above ~3% in each risk group were included (1 case in Low/Intermediate-risk, 4 cases in High-risk and 5 cases for the common fusion transcripts shared by Low/Intermediate-risk and high-risk groups).…”
Section: Discussionmentioning
confidence: 99%
“…These include EPAS1 (17) and MSX1 (18), both of which have been shown to inhibit neuroblastoma cell growth. Further analysis of our Wnt differentially expressed genes (DEGs) suggested that Wnt signalling is also a key regulator of mesenchymal and adrenergic differentiation states (19) which contribute to neuroblastoma cellular heterogeneity in both cell-lines and primary tumours (20,21).…”
Section: Our Previous Work Demonstrated High-levels Of the Leucine Rimentioning
confidence: 99%